Hepatocyte growth factor and epidermal growth factor in HIV infected women with preeclampsia. (September 2019) - Kupsamy, Kyle; Moodley, Jagidesa; Naicker, Thajasvarie
Abstract: Objectives: Epidermal growth factor (EGF) and Hepatocyte growth factor (HGF) both have tyrosine kinase receptors (EGFR and c-Met) which upon binding, activates and regulates many important cellular processes such as cell survival, growth, proliferation, differentiation, invasion, repair and so forth via the RAS/MAPK/ERK1/2, PI3K/AKT and JAK STAT3 pathways. These processes are crucial for the development of a placenta and other functions in order for a normal pregnancy to occur. Hence, this study determined the concentrations of HGF and EGF to find the correlation between HIV and preeclampsia (PE). Study design: A total sample size of n = 80 was used, n = 40 preeclamptic women and n = 40 normotensive women these were further stratified into HIV-positive and HIV-negative women. Analysis of the growth factors were done by using the multiplex Bio-Plex immunoassay method. Results: Irrespective of HIV status, based on pregnancy type, EGF in PE women displayed an upregulation compared to normotensive women. However, for HGF no variance was found between pregnancy type. Based on HIV status, regardless of pregnancy type, both HGF and EGF levels were significantly increased in HIV-positive women compared to HIV-negative women. Across all groups for HGF, significant difference was found between HIV-negative normotensive women (lower) vs HIV-positive normotensive women (higher). Nevertheless, for EGF across all groups, a statistically significant decrease was found in HIV-negative normotensive women compared to HIV-positive normotensive women, HIV-positive PE women and HIV-negative PE women. Conclusion: The study demonstrates that there is a strong association between HIV and PE and that HGF and EGF are promising biomarkers to use as a diagnostic tool for PE.